Sound Apperception Test: Development and Validation (Global Journal of Human-Social Science, 2015)
We report the development of Sound Apperception Test (SAT) measuring personality using an alternative, auditory form of projective testing. Sound effects designed to measure four personality dimensions, viz. intellectual functioning; interpersonal adjustment, task orientation and emotional embedded-ness were created. Stimulus analysis was carried out on a randomly drawn sample (n=440). Twenty-four out of the 60 sound effects had more than 75% consensus among expert raters and were retained. Six of the 18 sound effects were common for males and females, and six each were gender-specific. The test-retest reliability for males (n=107) was 0.692-0.765 (p< 0.01) and for females (n=69) it was 0.644-0.841 (p< 0.01). The validity for males (n=178) was 0.652-0.691 (p
Keywords: sound apperception test; tat; sound effect; sat